(untitled) (Islas, 2025)
Introduction: This article reviews three types of sound-producing archaeological artifacts from the indigenous cultures of Ecuador, aiming to explore and acknowledge them from various perspectives, including archaeological, transcultural, social, historical, and structural sound-based approaches. Methods: The methodology used is mixed, encompassing exploratory, ethnographic, technical-musicological, and deductive approaches, in order to evoke contemporary reflections of a transcultural, social, and historical nature, as well as potential meanings of the reviewed Ecuadorian archaeological sound artifacts. Results: The review of the selected archaeological sound artifacts confirms that the whistle bottle spread from equatorial territories to the north and south along the Pacific. The female figurines indicate the presence, authority, and status of women in past times; their acoustic system is exceptional, as is that of the conch flute, which features calendrical symbols such as the eight-pointed star. Conclusions: The acoustic systems, construction, and possible meanings of the analyzed archaeological sound artifacts reveal, through their unique characteristics, that they belong to fundamental and foundational Ecuadorian cultures whose creations spread to other American territories.